Exploring Talent Cultivation of College Student-Athletes for New Ventures and Entrepreneurial Psychology of New Venture Entrepreneur - Wang, Qinglei; Aman, Mohd Salleh; Hooi, Lim Boon (Frontiers in Psychology, 2021)
To further promote the development of new ventures, sufficient research and analysis has been conducted on the managers (especially, new venture entrepreneurs) and employees of new ventures. Here, the case investigation is adopted to study the psychological stress of new venture entrepreneurs and the psychological capital of college athletes and the cultivation of employability. The research results show that there is no significant difference in career guidance curriculum and employability among students with different academic performance (p>0.05), but there is a significant difference in psychological capital among students with different academic performance (p<0.05) The career guidance curriculum, employability, and psychological capital have different correlation degrees. The career guidance curriculum has a significantly positive impact on students' employability, and psychological capital plays a mediating role in the impact of the career guidance curriculum on employability. The analysis of the psychological stress of new venture entrepreneurs indicates that the stress of the dimension of resource requirements is the least. Meanwhile, the psychological stress of new entrepreneurs has a positive impact on new venture performance. The research content is fully considered, which can provide a scientific and effective reference for the follow-up research.